2023
DOI: 10.1038/s41420-023-01573-0
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation triggers mitophagy to enhance DNA damage in cancer cells

Abstract: Radiotherapy is an important cancer treatment strategy that causes DNA damage in tumor cells either directly or indirectly. Autophagy is a physiological process linked to DNA damage. Mitophagy is a form of autophagy, which specifically targets and eliminates impaired mitochondria, thereby upholding cellular homeostasis. However, the connection between DNA damage and mitophagy has yet to be fully elucidated. We found that mitophagy, as an upstream signal, increases ionizing radiation-induced DNA damage by downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…We observed variations in the median cell area, both across different cell lines within the same condition and within each cell line across radiation conditions. The median area of the cells increased after irradiation with 10 Gy, which agrees with previously observed cellular enlargement of irradiated cells [Rene and Nardone, 1968;Ronny Sham et al, 2020;Ren et al, 2023]. The UPCISCC131 cell line displayed the most increase in median cell area following irradiation.…”
Section: Resultssupporting
confidence: 90%
“…We observed variations in the median cell area, both across different cell lines within the same condition and within each cell line across radiation conditions. The median area of the cells increased after irradiation with 10 Gy, which agrees with previously observed cellular enlargement of irradiated cells [Rene and Nardone, 1968;Ronny Sham et al, 2020;Ren et al, 2023]. The UPCISCC131 cell line displayed the most increase in median cell area following irradiation.…”
Section: Resultssupporting
confidence: 90%
“…However, there is a disparity in the levels of cath L between the western blot and immunofluorescence results, which may be attributed to mitophagy. A study by Yanxian et al ( 2023) [53] previously demonstrated mitophagy in cells exposed to ionizing radiation, showing a dose-dependent increase in mitophagy. As a result, our hypothesis proposes that the intensified lysotracker red staining in the immunofluorescence images is not solely due to elevated specific cathepsin expression.…”
Section: Discussionmentioning
confidence: 96%
“…Another study showed that IR damages mitochondria by deforming them and initiates mitophagy in both PANC-1 and SW1990 cells by increasing the levels of the mitophagic sensors Parkin and BNIP3. After a period of 48 h following X-ray irradiation, it was observed that there was a rise in the spatial proximity between the lysosomes and mitochondria in both PANC-1 and SW199 cells [ 204 ]. The effect of high-dose irradiation leads to a decrease in the mitochondrial membrane potential, which correlates with defective protein import.…”
Section: Radiation-induced Cellular Senescencementioning
confidence: 99%